0.5 m Triboelectric Nanogenerator for Efficient Blue Energy Harvesting of All‐Sea Areas. Issue 35 (17th October 2022) - Feng, Junrui; Zhou, Hanlin; Cao, Zhi; Zhang, Enyang; Xu, Shuxing; Li, Wangtao; Yao, Huilu; Wan, Linyu; Liu, Guanlin
Abstract: Triboelectric nanogenerators (TENGs) to harvest ocean wave blue energy is flourishing, yet the research horizon has been limited to centimeter‐level TENG. Here, for the first time, a TENG shell is advanced for ocean energy harvesting to 0.5 m and an excellent frictional areal density of 1.03 cm −1 and economies of scale are obtained. The unique structure of the multi‐arch shape is adopted to untie the difficulty of fully getting the extensive friction layer contact. An inside steel plate is vertically placed in the center of every TENG block, which can activate the TENG to achieve complete contact even at a tilt angle of 7 degrees. The proposed half‐meter TENG (HM‐TENG) has a broad response band from 0.1 to 2 Hz, a total transferred charge quantity up to 67.2 µC, and one single TENG can deliver an open‐circuit voltage of 368 V. Coupled with the self‐stabilizing and susceptible features the ellipsoid shell brings, the HM‐TENG can readily accommodate itself to the all‐weather, all‐sea wave energy harvesting. Muchmore, the HM‐TENG is also applied to RF signal transmitters. This work takes the first step toward near‐meter‐scale enclosures and provides a new direction for large‐scale wave energy harvesting. Abstract : In this paper, for the first time, a TENG shell is advanced for ocean energy harvesting to 0.5 m and an excellent frictional areal density of 1.03 cm ‐1 and economies of scale are obtained. The HM‐TENG can readily accommodate itself to the all‐weather, all‐sea wave energy harvesting. Muchmore, the HM‐TENG is also applied to RF signal transmitters.